'There was no preamble': Comparing the Transition from Hospital to Home in Different Care Settings. Issue 2 (16th June 2021) - Saragosa, Marianne; Jeffs, Lianne; Hahn-Goldberg, Shoshana; Abrams, Howard; Soong, Christine; Hart, Michelle; Shea, Beverley; Okrainec, Karen
ABSTRACT: Our qualitative descriptive study compared how older patients and their informal caregivers experienced the care transition from acute care or rehabilitation to home. We recruited patients 65 years of age or older, or their informal caregivers, from in-patient units within acute care hospitals and rehabilitation facilities to participate in semi-structured interviews. We identified emergent themes via thematic analysis. In all, 16 patients and four patient caregivers participated. Across all care settings, caregivers were integral in facilitating the transition as well as experiencing variable discharge preparation, health care providers' optimizing transitions, and missed care and medication discrepancies at transition points. Orthopedic and rehabilitation patients more commonly voiced prior transition experiences in discharge preparation, including having to unexpectedly coordinate and wait for outpatient services. Differing responses between acute care and orthopedic settings suggest that transitional care practices and policies favor an individualized approach that considers patients' previous experiences, needs, and care expectations.